1981
DOI: 10.1029/ja086ia04p02242
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative simulation of a magnetospheric substorm 2. Comparison with observations

Abstract: Several results of the computer simulation of the behavior of the inner magnetosphere during the substorm‐type event of September 19, 1976, are discussed in detail. The model predicts a modest ring current injection, in to L ≈ 6, with total strength that is comparable to the strength estimated from the observed decrease in Dst. For the geosynchronous orbit region on the duskside, the model predicts a characteristic energy dispersion often observed by McIlwain and collaborators: energetic ions arrive first afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(42 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…For the presented cases, these regions of reduced ion concentration were rounded near the equatorward edges and more abrupt near the poleward edges. This is in accordance with the model predictions by Harel et al (1981a) and Harel et al (1981b), where the ionospheric currents would flow across a region of low conductivity, generating a peak in the electric field where the conductivity gradient was the sharpest, i.e. on its poleward side.…”
Section: Discussionsupporting
confidence: 74%
“…For the presented cases, these regions of reduced ion concentration were rounded near the equatorward edges and more abrupt near the poleward edges. This is in accordance with the model predictions by Harel et al (1981a) and Harel et al (1981b), where the ionospheric currents would flow across a region of low conductivity, generating a peak in the electric field where the conductivity gradient was the sharpest, i.e. on its poleward side.…”
Section: Discussionsupporting
confidence: 74%
“…The analytical treatment of Harel et al (1981) to some extent already establishes the point we wish to make. Their treatment uses for the energy lost to Joule heat the expression J T, where J is the injected particles' contribution to the ring current that generates Dst, is the transpolar potential, and T is the time the injected particles need to develop a complete ring.…”
Section: The Branching Ratio Of Injected To Dissipated Energymentioning
confidence: 99%
“…In the text they state as a generality, ''Statistical and case studies indicate that [during the expansion phase of a substorm] the predominant energy dissipation mechanism is Joule heating...'' They mean explicitly that Joule heating predominates over ''particle heating and plasma injection.'' One source they draw on for this assessment is the report of Harel et al (1981) on a quantitative substorm simulation using the Rice Convection Model. These authors find that ''global Joule heating...is about three times the change in ring current energy for the modeled substorm.''…”
Section: The Virial Theorem Applied To the Sub-storm Hypothesismentioning
confidence: 99%
“…References to an early observation (Galperin et al, 1973) and to subsequent clari®cations of the properties and signatures of these drifts (known as SAID) may be found in the work of Anderson et al, (1993), who investigated the temporal relationship between SAID and auroral substorms. A phenomenological model of SAID production, based on the ideas of Southwood and Wolf (1978) and Harel et al (1981), has been proposed by Anderson et al (1993) in order to account for the observed ionospheric signatures and their temporal relationship with substorms.…”
Section: A1mentioning
confidence: 99%